Molecular and phenotypic screening for submergence tolerance in lowland rice - Kar, R K; Mishra, T K; Pradhan, S K; Das, S R; Pandey, Ritu K (ORYZA-An International Journal of Rice, 2018)
Genetic variability was studied for yield and yield related traits in fifty one elite low land rice cultures, selected on the basis of their tolerance to submergence and stagnant flooding. The experimental materials possessed considerable amount of variability for all the traits. The genotypes were grouped into three clusters with ten sub-clusters on the basis of presence or absence of specific bands by using Sub1 specific SSRs markers. The cultivars like Savitri-Sub1, IR 64-Sub1, PSBRc 18-Sub1, Swarna-Sub 1, IR 85086-SUB 33-3-2-1, IR 87439-BTN-145-2-1, IR 88228-33-3-5-2, IR 88234-STG 11-1-1-1, IR 88250-20-1-1-3, IR 88764-SUB 30-1-1-2 and IR 88776-SUB 8-1-1-2 had shown high level of submergence tolerance through phenotyping. Submergence tolerancein these these lines were further validated through molecular screening using SSR markers. Amongst the molecular markers used, Sub1A 203, a direct marker is better for differentiating tolerant from intolerant to submergenceas compared to AEX, Sub1BC2 and RM 8300 for marker-assisted breeding program. Besides, it may be inferred that role of Sub1B and Sub1C may be ignored for submergence tolerance.